2019
DOI: 10.1212/wnl.0000000000006742
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and time course of epilepsy and the associated cognitive decline in MECP2 duplication syndrome

Abstract: ObjectiveWe characterized the epilepsy features and contribution to cognitive regression in 47 patients with MECP2 duplication syndrome (MDS) and reviewed these characteristics in over 280 MDS published cases.MethodsThe institutional review board approved this retrospective review of medical records and case histories of patients with MDS.ResultsThe average age at enrollment was 10 ± 7 years. Patients with epilepsy were older (13 ± 7 years vs 8 ± 5 years, p = 0.004) and followed for a longer time (11.8 ± 6.5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 29 publications
(55 reference statements)
4
60
1
1
Order By: Relevance
“…However, while severity of MECP2 mutations is linked to the RTT clinical phenotype, MECP2 duplication size and gene content predict neither presence of epilepsy, seizure type, age of seizure onset or responsiveness to treatment. Mechanisms by which MECP2 gene duplications modulate the spectrum and severity of neurocognitive phenotype remain unclear [ 199 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, while severity of MECP2 mutations is linked to the RTT clinical phenotype, MECP2 duplication size and gene content predict neither presence of epilepsy, seizure type, age of seizure onset or responsiveness to treatment. Mechanisms by which MECP2 gene duplications modulate the spectrum and severity of neurocognitive phenotype remain unclear [ 199 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown there is a possibility of regression in MDS (Peters, Hundley, Wilson, Carvalho, et al, 2013) that occurs at a much older age as compared to RTT. Developmental regression is likely to coincide with the onset of epilepsy in MDS (Marafi et al, 2019), and both are increasingly likely as participants age (Marafi et al, 2019; Peters et al, 2019). A recent study indicated that epilepsy affected around 47% of participants with MDS, disproportionately affected those who were older, and it was treatment‐refractory and consistent with epileptic encephalopathy in a high percentage of those cases (Marafi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental regression is likely to coincide with the onset of epilepsy in MDS (Marafi et al, 2019), and both are increasingly likely as participants age (Marafi et al, 2019; Peters et al, 2019). A recent study indicated that epilepsy affected around 47% of participants with MDS, disproportionately affected those who were older, and it was treatment‐refractory and consistent with epileptic encephalopathy in a high percentage of those cases (Marafi et al, 2019). Lennox–Gastaut Syndrome (LGS), a classic epileptic encephalopathy, was diagnosed in almost 25% of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…MECP2 is reported to be associated with a severe epileptic seizure phenotype in Rett syndrome (RTT) and in MECP2 duplication syndrome (MDS). 48,49 RTT is an X-linked neurodevelopmental disorder that primarily occurs in females. 50 Mutations of the gene encoding MECP2, which have been identified in 90%-95% of RTT cases, are considered to be the foremost cause of typical RTT.…”
Section: Discussionmentioning
confidence: 99%